Chinese education models in a global age - Zhou, Zhuying; Spangler, Jonathan 1971- (Singapore Springer, 2016)
China's rise, an increasing emphasis on international education benchmarking, and a global recognition of East Asian countries' success in this regard have brought the issue of Chinese education to the forefront of public consciousness. In particular, the concept of a zChinese education modely is one that has sparked debate and quickly become a major focus of education research around the world, especially in light of regional achievements vis-áa-vis university rankings, bibliometric indices, the Programme for International Student Assessment (PISA), Trends in International Mathematics and Science Study (TIMSS), and other such benchmarks. Chinese Education Models in a Global Age tackles this controversial issue head on by synthesizing a diversity of analyses from a world-class team of twenty-seven authors. It reveals that Chinese education models, which are present in many different geographic and institutional contexts, have an important influence on social and institutional norms as well as individual belief systems and behaviors in China and beyond. The first of its kind, this edited volume establishes a foundation for future research while providing a nuanced and tightly integrated compilation of differing perspectives on the role and impact of Chinese education models worldwide. It is essential reading for all scholars, policymakers, students, parents, and educators interested in the rising demographic and economic influence of people of Chinese descent on education around the world.
4.5.3 Curriclum Wisdoms in Chinese Philosophical Traditions4.6 Conclusion: Expanding Horizons of Curriculum Wisdoms; References; Chapter 5: A Study of Educational Policies Relating to Afterschool Programs and Educational Equality in Taiwan; 5.1 Introduction; 5.2 Minorities, Disadvantaged Students, and Schooling; 5.3 Disadvantaged Students, Afterschool Programs, and Remedial Teaching; 5.4 A New Approach to Remedial Teaching of Math; 5.4.1 Research on Remedial Teaching in Math; 5.4.2 Develop Professional Resources and Supporting Systems for Remedial Teaching in Math.
Includes bibliographical references and index.
Keywords: Education -- China